2017
DOI: 10.1007/s13197-017-2490-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters for the production of collagen peptides from fish skin (Epinephelus malabaricus) using response surface methodology and its characterization

Abstract: The study optimized the hydrolysis conditions for the production of fish collagen peptides from skin of Malabar grouper () using response surface methodology. The hydrolysis was done with enzymes pepsin, papain and protease from bovine pancreas. Effects of process parameters viz: pH, temperature, enzyme substrate ratio and hydrolysis time of the three different enzymes on degree of hydrolysis were investigated. The optimum response of degree of hydrolysis was estimated to be 10, 20 and 28% respectively for pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…It is a technique where peptides are first mixed with a large molar excess of a matrix compound such as DHB (2,5-dihydroxybenzoic acid) to ionize low-molecular-weight peptides, next the matrix that carries the peptides is vaporized by laser radiation, and finally the mass of vaporized peptides is determined from the ionic time-of-flight. However, the limitation of this technique is that some peptide peaks fail to resolve in a single matrix [61,62,63].…”
Section: Hydrolyzed Collagen: Extraction and Propertiesmentioning
confidence: 99%
“…It is a technique where peptides are first mixed with a large molar excess of a matrix compound such as DHB (2,5-dihydroxybenzoic acid) to ionize low-molecular-weight peptides, next the matrix that carries the peptides is vaporized by laser radiation, and finally the mass of vaporized peptides is determined from the ionic time-of-flight. However, the limitation of this technique is that some peptide peaks fail to resolve in a single matrix [61,62,63].…”
Section: Hydrolyzed Collagen: Extraction and Propertiesmentioning
confidence: 99%
“…Accordingly, protein hydrolysates and peptides from various cheap and underutilized marine sources, such as fish muscles and byproducts, and microalgae have been widely used to produce antioxidant protein hydrolysates and peptides. For example, Atlantic salmon (Auwal et al, 2017), Chub marckerel (Bashir et al, 2017), Acetes indicus (Dhanabalan et al, 2017), Epinephelus malabaricus skin (Hema et al, 2017), Turbot skin (Fang et al, 2017), Shrimp shell discards (Ambigaipalan and Shahidi, 2017), Tilapia frame and skin (Huang et al, 2015), Blue-green algae (Seddek et al, 2019), Irish brown seaweed (Kadam et al, 2016), Tetradesmus obliquus microalgae (Montone et al, 2018b) have been reported as sources of antioxidant peptides.…”
Section: Source Of Antioxidant Peptidesmentioning
confidence: 99%
“…Protein extraction from fish and animal products is not that much difficult like obtaining protein isolate from plant and algae sources. The preliminary process involves cleaning of the source materials thoroughly with tap water to remove any foreign maters and separating the meat from the skin and bones (Dhanabalan et al, 2017;Hema et al, 2017). Afterward, the required part of the materials are mixed with distilled water containing sufficient amount of solvent, commonly Hexane, and centrifuged to remove oil components (Bashir et al, 2017).…”
Section: Fish Typementioning
confidence: 99%
See 2 more Smart Citations